The Principal's Leadership Style and the Teacher Performance - Sutarjo Sutarjo; Muhammad Kristiawan; Rambat Nur Sasongko (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The principal's leadership style as a leader will impact the effectiveness of enhancing teacher performance under his guidance. The goal of this study was to collect information on (1) the principal's leadership style, (2) the execution of the  principal's leadership style, and (3) the restrictions that the principal faces in enhancing teacher performance in schools. Data collecting approaches were carried out using a qualitative approach with descriptive methodologies, including interviews, observations, and documentation. This study demonstrates that (1) the principal employs a situational leadership style in influencing his subordinates by viewing and comprehending each of his subordinates' backgrounds while creating policies. (2) Use of the principal's leadership style to influence teacher performance, namely instructional, consultative, participative, and delegative leadership. (3) The difficulties that school principals encounter include the limited competence of instructors to use "computer" technology, the lack of flexibility in the selection of learning techniques used by the teacher, and the diverse backgrounds of the subordinates.